2013
DOI: 10.4187/respcare.02674
|View full text |Cite
|
Sign up to set email alerts
|

Endurance Time Is the Most Responsive Exercise Measurement in Idiopathic Pulmonary Fibrosis

Abstract: BACKGROUND: Although pulmonary rehabilitation (PR) has been reported to improve exercise capacity in patients with idiopathic pulmonary fibrosis, it is unknown which exercise measurement is the most responsive for evaluation of PR efficacy. The purpose of this study was to compare the responsiveness of 5 exercise measurements by evaluating the efficacy of PR in subjects with idiopathic pulmonary fibrosis. METHODS: We conducted a prospective observational study in which 53 subjects with idiopathic pulmonary fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 30 publications
4
56
1
2
Order By: Relevance
“…In contrast, Huppmann et al [34] and Ryerson et al [35] showed higher improvement rates in 6MWD following pulmonary rehabilitation programs in the most deconditioned ILD patients and those with low baseline values, respectively [34,35]. Our findings are also in concordance with a recent report by Arizono et al [36], who also showed significant improvements of CPET parameters in IPF patients, but not V O 2 peak. Following the intervention we also found significant improvements in pulmonary and ventilatory parameters in the ET group (table 2).…”
Section: Discussionsupporting
confidence: 63%
“…In contrast, Huppmann et al [34] and Ryerson et al [35] showed higher improvement rates in 6MWD following pulmonary rehabilitation programs in the most deconditioned ILD patients and those with low baseline values, respectively [34,35]. Our findings are also in concordance with a recent report by Arizono et al [36], who also showed significant improvements of CPET parameters in IPF patients, but not V O 2 peak. Following the intervention we also found significant improvements in pulmonary and ventilatory parameters in the ET group (table 2).…”
Section: Discussionsupporting
confidence: 63%
“…a 100-s or 33% improvement was reached in 30 (91%) out of 33 and 27 (82%) out of 33 investigations, respectively) (figure 1). tLIM is also responsive to rehabilitation in idiopathic PAH [121,122] and IPF [123,124]. In one observational study of 53 IPF patients, the effect size for tLIM after rehabilitation was larger than for V′O 2 peak, WRpeak, 6MWD and ISWT [123] (table 3).…”
Section: Discussionmentioning
confidence: 99%
“…tLIM is also responsive to rehabilitation in idiopathic PAH [121,122] and IPF [123,124]. In one observational study of 53 IPF patients, the effect size for tLIM after rehabilitation was larger than for V′O 2 peak, WRpeak, 6MWD and ISWT [123] (table 3). Oxygen therapy significantly increases tLIM by an average of 162 (95% CI 118-207) s in patients with COPD who desaturate during exercise [59].…”
Section: Discussionmentioning
confidence: 99%
“…Other tests of exercise capacity may have greater sensitivity to change following PR. A comparison of five exercise measurements (endurance time, peak work rate, peak oxygen consumption, 6MWD, and SWT) at the beginning and end of PR in patients with IPF found cycle endurance time was the most responsive [Arizono et al 2014].…”
Section: Pulmonary Rehabilitation: Outcome Assessmentmentioning
confidence: 99%